Red blood cells derived from whole blood treated with riboflavin and ultraviolet light maintain adequate survival in vivo after 21 days of storage. Issue 5 (31st March 2017) - Cancelas, Jose A.; Slichter, Sherrill J.; Rugg, Neeta; Pratt, P. Gayle; Nestheide, Shawnagay; Corson, Jill; Pellham, Esther; Huntington, Marty; Goodrich, Raymond P.
Abstract : BACKGROUND: Pathogen reduction (PR) of whole blood (WB) may increase blood safety when applied before component separation. This study evaluates the in vivo performance of red blood cells (RBCs) derived from WB treated with the riboflavin and ultraviolet (UV) light PR (Mirasol) system. STUDY DESIGN AND METHODS: This was a prospective, two‐center, single‐blind, randomized, two‐period, crossover clinical trial designed to evaluate autologous 51 Cr/ 99m Tc‐radiolabeled recovery and survival of RBCs derived from Mirasol‐treated WB compared to untreated WB. RBCs were stored in AS‐3 for 21 days at 1 to 6°C. In vitro RBC variables were characterized. Frequency and severity of treatment‐emergent adverse event (TEAE) and neoantigenicity were determined. RESULTS: Twenty‐four healthy adult volunteers (n = 12 per site) were evaluated. The Mirasol 24‐hr RBC recoveries were 82.5 ± 3.9% with one‐sided 95% lower confidence limit of 80.9%, meeting US Food and Drug Administration acceptance criteria, albeit at lower level than controls (91.7 ± 6.8%, p < 0.001). Mean RBC survival and T50 were reduced in the Mirasol group (61 and 23 days, respectively) versus controls (82 and 36 days, respectively; p < 0.001) with a mean area under the curve survival of treated RBCs of 83% of untreated controls. End‐of‐storage hemolysis in the Mirasol group was 0.22 ± 0.1% (control, 0.15 ± 0.1%; p < 0.001). No neoantigenicity or differences in TEAEs were found. CONCLUSION: RBCs derived from Mirasol WB and stored for up to 21 days in AS‐3 maintained acceptable cell quality and recovery, albeit modestly reduced compared with untreated RBCs. Mirasol WB may represent a valid single WB PR platform that allows manufacture of RBC for storage for up to 21 days.